Kajian Foto Udara dan Sistem Informasi Geografis untuk Pemetaan Kondisi Peresapan Air Sub DAS Wedi Kabupaten Klaten, Jawa Tengah - Agus Anggoro Sigit; Dulbahri Dulbahri; Suyono Suyono (Fakultas Geografi, Universitas Gadjah Mada, 2010)
ABSTRACT The study was conducted in Klaten Regency at Wedi Sub Watershed, part of Dengkeng Watershed. The study aimed to: 1) study the interpretation accuracy of black and white Panchromatic Aerial Photograph scaling 1: 50.000 in identifying the soil factor, slope, landuse, vegetation density, and land conversation, related to the influences toward water infiltration condition in the research area; 2) make the zonation of infiltration capability and water infiltration condition based on land factors the result of aerial photograph interpretation; and 3) study the spatial distribution pattern of water infiltration condition in the research area and analyze to the distribution according to spatial. The research method used aerial photograph interpretation with supported by limited survey for field test, by sampling method was stratified sampling. The method of analysis applied spatial analysis by using Geographical Information System (GIS). The result of the study showed that: 1) the level of aerial photograph accuracy for interpreting determinate factors of water infiltration in the research area is acceptable each with the accuracy level of: slope 89.47%; soil texture 82.14%; land use 90.16%; vegetation density 88.89%; and land conservation 80.88%. It mean that although the accuracy level achieved had not been included in very good category, the aerial photograph still can be used in this study; 2) the condition of water infiltration in the research area tended to be relative still good, indicated by the of the land unit in status of ‘critical’ in the width no more than 25% (30.496 km2). The land unit in status of ‘begin to be rather critical’ in the width of 55.692 km2 or 50.97 %; while the remaining 3.154 km2 or 20.62% was in the status of ‘natural normal’ and 22.544 km2 or 20.62% had ‘good’ status; 3) In the research area, the space of land units with the condition of good infiltration had no spatial relevance to the space of land units and the great infiltration capability.